2012
DOI: 10.1126/science.1222981
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architecture and Assembly Principles of Vibrio cholerae Biofilms

Abstract: In their natural environment, microbes organize into communities held together by an extracellular matrix composed of polysaccharides and proteins. We developed an in vivo labeling strategy to allow the extracellular matrix of developing biofilms to be visualized with conventional and super-resolution light microscopy. Vibrio cholerae biofilms displayed three distinct levels of spatial organization: cells, clusters of cells, and collections of clusters. Multiresolution imaging of living V. cholerae biofilms re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
336
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 349 publications
(358 citation statements)
references
References 39 publications
(51 reference statements)
16
336
0
1
Order By: Relevance
“…This result was observed both in the presence and in the absence of invading cells, and it is consistent with previous reports documenting that V. cholerae biofilms lacking RbmA are structurally weaker than biofilms possessing the full complement of matrix proteins (Fong et al, 2006;Absalon et al, 2011;Berk et al, 2012;Giglio et al, 2013;Maestre-Reyna et al, 2013).…”
Section: Resident Biofilms Resist Internal Invasion By Conspecificssupporting
confidence: 81%
See 3 more Smart Citations
“…This result was observed both in the presence and in the absence of invading cells, and it is consistent with previous reports documenting that V. cholerae biofilms lacking RbmA are structurally weaker than biofilms possessing the full complement of matrix proteins (Fong et al, 2006;Absalon et al, 2011;Berk et al, 2012;Giglio et al, 2013;Maestre-Reyna et al, 2013).…”
Section: Resident Biofilms Resist Internal Invasion By Conspecificssupporting
confidence: 81%
“…Structural studies suggest that RbmA binds motherdaughter cell pairs together, linking them to polysaccharide components of the extracellular matrix (Giglio et al, 2013;Maestre-Reyna et al, 2013). Relative to biofilms expressing the full complement of matrix components, biofilms lacking RbmA exhibit poor sub-cluster coherence (Absalon et al, 2011;Berk et al, 2012). We hypothesized that the absence of RbmA could render V. cholerae biofilms susceptible to invasion by planktonic cells.…”
Section: Resident Biofilms Resist Internal Invasion By Conspecificsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one recent study, it was shown that Vibrio cholerae biofilm formation is characterized by changes in matrix composition during early stages biofilm growth, in which an envelope made up of different types of polysaccharides and proteins enclose cell clusters and was found to be capable of stretching and expanding to accommodate cell growth. [50]. These observations have not been addressed in the context of membrane biofouling, but could be important considering the composition of feedwater with respect to potential early colonisers.…”
Section: Hydrophobicitymentioning
confidence: 99%